The Influence of Personal Selling and Promotion Through Social Media on Tourists' Decisions in Buying Fishing Tour Packages in the Coastal Areas of Bali - Prayogi, Putu Agus; Paramita Sari, Ni Komang Julyanti (Akademi Komunitas MAPINDO, 2023)
The purpose of this study was to analyze the effect of promotion on social media and personal selling on guests' decisions in buying fishing tour packages in the coastal areas of Bali. This study used the purposive sampling method to analyze it, samples from guests who had used fishing tour packages in the coastal areas of Bali. Data was taken from 60 customers. It is analyzed with Regression Analysis Technic, it has been validated, reliability, and classical assumptions. Research shows that 1) Promotion on social media has a positive and significant effect on purchasing fishing tour packages in Bali's coastal areas; 2) Personal selling has a positive and significant effect on the decision to buy fishing tour packages in the coastal areas of Bali;3) Promotions on social media and personal selling have a positive and significant effect on the decision to buy fishing tour packages in the coastal areas of Bali; 4) The variable effect of promoting through social and personal media becomes the guest's decision to purchase a fishing package in the coastal area; and 5) The personal selling variable is more dominant in influencing the purchasing decision of fishing tour packages in the coastal areas of Bali. The implication of this study is the management of Bali's coastal areas to increase promotion through social media and personal selling to get customer intentions and they make the decision to buy fishing tour packages in the coastal areas of Bali Keywords: Promotion trough social media, Personal selling, Buying decision.